Supply of crab larvae to an estuary in the eastern Atlantic upwelling system exhibits predictable and haphazard variation at different temporal scales - Domingues, C. P. (2018)
We measured variability in daily supply levels of shore crab megalopae in an estuary on the northwest Portuguese coast, Ria de Aveiro, located in the eastern Atlantic upwelling system. The 5 yr study covered the shore crab larval season (generally February to July) in 2002 and from 2006 to 2009. We addressed the possible effects of wind- and tide-driven circulation, number of flood hours during darkness, and chlorophyll a concentration in coastal waters on larval supply variation. Megalopae supply measured over the years was an episodic phenomenon, and observations showed some predictable and haphazard patterns. In some episodes, supply was highest around spring tides and was enhanced by southerly winds, as predicted, although not all episodes fitted this pattern. The relationships between supply levels and number of flood hours during darkness or chlorophyll a concentration were ambiguous throughout the time series, although in some years increased levels of supply were positively correlated with number of flood hours during the night. The analysis of multiple years conducted in this study showed that shore crab megalopae supply patterns to Ria de Aveiro are more variable than previously assumed, suggesting the participation of several delivery mechanisms that vary within and among years. However, a proportion of supply variation exists that cannot be explained by the mechanisms we propose.